Seven Habits of Great Teachers worth Emulating in Teaching Students - Ilmi, Aisyah Raudhatul; Muslim, Hanifa; Salaeh, Ibnu Muhammad Yamudin (Khalifa: Journal of Islamic Education, 2023)
This study aims to explore teachers’ efforts in addressing students’ problems in Islamic boarding schools. The research employed a qualitative method with an ethnographic approach. Data were collected from eleven informants, consisting of teachers and students, through interview protocols. To support the interview data, the researcher conducted field observations for three months by directly participating in classroom activities. All interview and observation data were analyzed thematically using the Miles and Huberman data analysis model. The results indicate seven types of efforts undertaken by teachers to deal with students’ problems in Islamic boarding schools: i) understanding students, ii) providing motivation, iii) giving advice, iv) creating engaging learning experiences, v) conducting special learning sessions, vi) collaborating with parents, and vii) implementing ta’zir (disciplinary actions). These findings suggest that teachers play a significant role in managing students’ challenges and may serve as a useful reference for other Islamic boarding schools in developing strategies to handle similar issues.